TEACHER TALK CATEGORY IN FLINT USED BY ENGLISH TEACHER AT SMA YPK MEDAN - Ronatama Sari Nababan; Sumarsih Sumarsih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
This research deals with developing writing materials about descriptive text through facebook group for eight grade junior high school. The research was conducted to examine the initial condition of students before using the descriptive text materials developed through FB and to develop the materials through FB for the teaching descriptive text. This research was conducted at SMP Swasta Jambi Medan. This research was conducted by using Research and Development design through six stages; gathering information and data, analyzing data, developing materials and media, validating by expert, revising, and final product. The subject of this research was eight grade of SMP Swasta Jambi Medan. The data were gathered by reviewing documents, conducting interview to English Teacher, and distributing questioner to eight grade consist of 26 students to get the students’ need. The interview and questioner result prove that the students need interesting materials about descriptive text and media. The developed writing materials was validated by expert which average score 3,5 show that the writing materials are valid and suitable to use for grade eight SMP Swasta Jambi Medan. The result of the product distributed to the students through Facebook.Key words: Development, Writing Materials, Facebook.